2019
DOI: 10.1038/s41598-019-46449-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the local asymmetry in the hydrogen bond network of liquid water by an ultrafast electric field pulse

Abstract: Condensed phase electron decomposition analysis based on density functional theory has recently revealed an asymmetry in the hydrogen-bond network in liquid water, in the sense that a significant population of water molecules are simultaneously donating and accepting one strong hydrogen-bond and another substantially weaker one. Here we investigate this asymmetry, as well as broader structural and energetic features of water’s hydrogen-bond network, following the application of an intense electric field square… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…Of special note, this electrokinetic confined or trapped water exhibits a quantum tunneling behavior [ 115 ]. These data suggest that the interfacial water is a potential target for the effects of REMFS, which is confirmed by other investigators that proposed that water is a sensor for low energy EMF [ 116 ].…”
Section: Remfs Mechanism At the Quantum Levelsupporting
confidence: 87%
“…Of special note, this electrokinetic confined or trapped water exhibits a quantum tunneling behavior [ 115 ]. These data suggest that the interfacial water is a potential target for the effects of REMFS, which is confirmed by other investigators that proposed that water is a sensor for low energy EMF [ 116 ].…”
Section: Remfs Mechanism At the Quantum Levelsupporting
confidence: 87%
“…The effect of an electric field on the local HB asymmetry in water was investigated with AIMD using an intense electric field square pulse with an intensity of 4.3 × 10 9 V m −1 . 61 The pulse strength was chosen such that it induces an ultrafast re-orientation of the water molecules on a sub-picosecond time scale. Under these conditions, it was shown that within 300 fs, the water molecules reach a steady-state average orientation angle of 37 degrees ( cos(θ ) ≈ 0.8), where the angle is calculated between the molecular bisector and the direction of the external field.…”
Section: Enhancement Of Asymmetry Under External Electric Fieldsmentioning
confidence: 99%
“…[10][11][12] In this article, we are going to review some of our efforts in unraveling a particular aspect of water's HB network, which is the local asymmetry in the strengths of HBs donated or accepted from/to a water molecule in bulk liquid water under ambient conditions. 9,13,14,21,40,43,48,61 While it is well known that the HB strength in water or in ice exhibit a broad distribution trivially due to thermal fluctuations, the novel and non-trivial aspect that was revealed is that in liquid water (but not in hexagonal ice), thermal motion leads to a significant population of molecules, where the strength of the two donor or acceptor interactions have an extreme disparity with as much as 25% of the molecules having one donor (acceptor) interaction that is more than six times stronger than the other donor (acceptor) interaction, and a significant pop-ulation having both kinds of interactions highly asymmetric. This interesting feature of water's HB network was revealed using ab initio molecular dynamics (AIMD) simulations ?…”
Section: Introductionmentioning
confidence: 99%
“…The superior efficiency of this method originates from the fact that only one preconditioned gradient computation is necessary per AIMD step. In fact, a gain in efficiency between one to two orders of magnitude has been observed for a large variety of different systems ranging from molecules and solids [238][239][240][241][242][243][244][245], including phase-change materials [246][247][248][249][250][251][252], over aqueous systems [253][254][255][256][257][258][259][260][261], to complex interfaces [262][263][264][265][266][267][268].…”
Section: B Second-generation Car-parrinello Molecular Dynamicsmentioning
confidence: 99%
“…The ALMO EDA has been applied to study intermolecular interactions in a variety of gas-and condensed-phase molecular systems [288,290]. The CP2K implementation of ALMO EDA has been particularly advantageous to understand the nature of hydrogen bonding in bulk liquid water [208,214,216,255,258,259,261,289], ice [291] and water phases confined to low dimensions [292]. Multiple studies have pointed out a deep connection between the donor-acceptor interactions and features of the X-ray absorption [214,293], infrared (IR) [255,256,258,261,289,294,295] (Fig.…”
Section: A Energy Decomposition Analysis Based On Compact Localized M...mentioning
confidence: 99%